2021
DOI: 10.1371/journal.pone.0246103
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices towards rabies: A survey of the general population residing in the Harare Metropolitan Province of Zimbabwe

Abstract: Background Rabies remains endemic to the Harare Metropolitan Province of Zimbabwe, with a lack of public participations potentially contributing to the limited success in eliminating the disease. We hypothesized that rabies intervention campaigns were less successful than they could be as a result of poor understanding of the disease at the community level, and thus aimed to identify the knowledge, attitudes, and practices towards rabies in the province. Methods A cross-sectional survey, using a semi-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A study conducted in Zimbabwe showed that 49% of the inhabitants had at least a dog or a cat; the estimated human population of 2.8 million people had approximately 175 000 dogs living with them, a situation that is similar to our population, since most accidents take place in the home. 13 In Nepal, a similar problem has been described in relation to stray dogs. 14 Brazil has reported a high incidence of animal attacks in urban areas in relation to social vulnerability, disorderly urbanization, and the large number of pets.…”
Section: Discussionmentioning
confidence: 86%
“…A study conducted in Zimbabwe showed that 49% of the inhabitants had at least a dog or a cat; the estimated human population of 2.8 million people had approximately 175 000 dogs living with them, a situation that is similar to our population, since most accidents take place in the home. 13 In Nepal, a similar problem has been described in relation to stray dogs. 14 Brazil has reported a high incidence of animal attacks in urban areas in relation to social vulnerability, disorderly urbanization, and the large number of pets.…”
Section: Discussionmentioning
confidence: 86%
“…Un estudio en Zimbabue demostró que el 49 % de los habitantes tenía al menos un perro o un gato; la población humana estimada de 2,8 millones de personas tenía aproximadamente 175 000 perros residiendo con ellos, situación que podría compararse con nuestra población, ya que la mayoría de los accidentes son domiciliarios. 13 En Nepal, se describe una problemática similar, con relación a perros callejeros. 14 Brasil reporta alta incidencia de accidentes por animales en áreas urbanas, debido a la vulnerabilidad social, urbanización desordenada y la gran cantidad de animales domésticos.…”
Section: Discussionunclassified
“…As a first step, a univariable logistic regression analysis was used to calculate the odds ratios (ORs) and corresponding 95% confidence intervals (CI) for the captured socio-demographic characteristics. Thereafter, a forward stepwise multivariate logistic regression analysis was undertaken as described elsewhere [ 25 , 26 ]. To assess confounding effects, predictor variables that were not selected for the final logistic regression model were added and their impact on the coefficient of the predictor variables determined as described elsewhere [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, a forward stepwise multivariate logistic regression analysis was undertaken as described elsewhere [ 25 , 26 ]. To assess confounding effects, predictor variables that were not selected for the final logistic regression model were added and their impact on the coefficient of the predictor variables determined as described elsewhere [ 25 , 26 ]. No such confounders were detected in this study and the adjusted OR (aOR) and their corresponding 95% CIs were derived.…”
Section: Methodsmentioning
confidence: 99%